Contribution of Hindustani Classical Music to the Creation of the Brand Bollywood and Using the Business as a Global Soft Power - Bandukwalla, Tannaz (Digital Repository of Theses - SSBM Geneva, 2024)
The study aims to identify the impact of Hindustani Classical Music on the Bollywood industry. The study defines how Bollywood emerged with the help of Hindustani classical music. The study utilizes a mixed research design to leverage the advantages of qualitative and quantitative methods. The study's target group consists of individuals worldwide who are interested in Bollywood films and music. The business concept of assimilating Hindustani Classical Music and Bollywood investigates how Bollywood may be used to increase India's cultural impact on the international arena. Indian traditional musical aspects were blended into mainstream film, allowing Bollywood to build unique cultural brands and resonate them with the worldwide cinematic industry. The study finds that Hindustani classical music has had a significant impact on the rise of the Bollywood industry. There is a scarcity of research examining the significance of Hindustani classical music in the cinema business. The study suggests that the Importance of Hindustani classical music in the Bollywood industry needs to be more examined. This promotes India's economic prospects in cultural diplomacy at the global level through cinematography. It expands India's business opportunities in the global entertainment sector.